A High‐Performance Hybrid Biofuel Cell with a Honeycomb‐Like Ti3C2Tx/MWCNT/AuNP Bioanode and a ZnCo2@NCNT Cathode for Self‐Powered Biosensing. Issue 10 (22nd December 2022) - Sun, Yuping; Qin, Tengteng; Liu, Xiaoqiang; Liu, Yuan; Zhao, Dan; Wong, Danny K.Y.
Abstract: This work focusses on developing a hybrid enzyme biofuel cell‐based self‐powered biosensor with appreciable stability and durability using murine leukemia fusion gene fragments (tDNA) as a model analyte. The cell consists of a Ti3 C2 T x /multiwalled carbon nanotube/gold nanoparticle/glucose oxidase bioanode and a Zn/Co‐modified carbon nanotube cathode. The bioanode uniquely exhibits strong electron transfer ability and a high surface area for the loading of 1.14 × 10 −9 mol cm −2 glucose oxidase to catalyze glucose oxidation. Meanwhile, the abiotic cathode with a high oxygen reduction reaction activity negates the use of conventional bioenzymes as catalysts, which aids in extending the stability and durability of the sensing system. The biosensor offers a 0.1 fm –1 nm linear range and a detection limit of 0.022 fm tDNA. Additionally, the biosensor demonstrates a reproducibility of ≈4.85% and retains ≈87.42% of the initial maximal power density after a 4‐week storage at 4 °C, verifying a significantly improved long‐term stability. Abstract : This work focuses on a hybrid enzyme biofuel cell with a self‐powered biosensor for tDNA. It consists of a Ti3 C2 T x /multiwalled carbon nanotube/gold nanoparticle/glucose oxidase bioanode, which offers strong electron transfer ability and a high surface area for accommodating abundant enzyme, and a Zn/Co‐modified carbon nanotube cathode without any conventional catalysts for oxygen reduction reaction.